PsycEXTRA Dataset 2008
DOI: 10.1037/e513082008-001
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and behavioral outcomes in sheltered homeless children: The moderating role of perceived social support

Abstract: This study examined the association between traumatic exposure and mental health outcomes in sheltered homeless children. Also investigated was the moderating role of perceived social support in the pathway between traumatic exposure and emotional distress. Trauma exposure was conceptualized in two ways: first through lifetime exposures to abuse, neglect, negative peers, community and interpersonal violence, and the loss of significant attachment figures, and; second through highly stressful events that occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…Additionally, they evidence higher than average rates of learning disabilities and poor classroom behaviors and are more likely than their peers to perform poorly on standardized assessments of reading and math (Fantuzzo & Perlman, 2007; Obradovic et al., 2009; Perlman & Fantuzzo, 2010; Rafferty, Shinn, & Weitzman, 2004). In terms of their psychological well‐being, children who have experienced homelessness are more likely than their peers to have experienced traumas such as domestic violence and child maltreatment (Buckner, Bassuk, & Zima, 1993; Cowan, 2007; Hicks‐Coolick, Burnside‐Eaton, & Peters, 2003; Lindsey, 1998; Perlman & Fantuzzo, 2010). Rates of anxiety, depression, and posttraumatic stress are high in this population of children (Cowan, 2007).…”
Section: Homelessness and The Impact On Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they evidence higher than average rates of learning disabilities and poor classroom behaviors and are more likely than their peers to perform poorly on standardized assessments of reading and math (Fantuzzo & Perlman, 2007; Obradovic et al., 2009; Perlman & Fantuzzo, 2010; Rafferty, Shinn, & Weitzman, 2004). In terms of their psychological well‐being, children who have experienced homelessness are more likely than their peers to have experienced traumas such as domestic violence and child maltreatment (Buckner, Bassuk, & Zima, 1993; Cowan, 2007; Hicks‐Coolick, Burnside‐Eaton, & Peters, 2003; Lindsey, 1998; Perlman & Fantuzzo, 2010). Rates of anxiety, depression, and posttraumatic stress are high in this population of children (Cowan, 2007).…”
Section: Homelessness and The Impact On Childrenmentioning
confidence: 99%
“…Once in emergency or temporary shelter, the structure of families may be impacted by shelter regulations regarding the number and gender of residents. Some shelters limit the number of children who may accompany parents, whereas others may outright bar older children and adolescents, especially boys (Cowan, 2007). These regulations may create an elevated risk of foster care placement for the children and youth who are separated from their parents.…”
Section: Contextual and Relationship Risk Factorsmentioning
confidence: 99%
“…Homelessness is associated with a higher incidence of exposure to traumatic events (Anooshian, 2005; Cowan, 2007; Guarino & Bassuk, 2010; Hicks-Coolick et al, 2003; Perlman & Fantuzzo, 2010), complex trauma (i.e., polyvictimization or prolonged exposure to trauma), and adverse childhood experiences, including poverty, family and housing instability, separation from caregivers, community violence, and decreased access to health care and educational services (Masten et al, 1997; Panter-Brick, 2004; Shelton et al, 2015; Zlotnick, 2009).…”
Section: Mental Health Needs Of Young Children Experiencing Homelessnessmentioning
confidence: 99%
“…Homeless children have high rates of exposure to interpersonal and chronic community violence (Bassuk, Dawson, et al. 2001; Bassuk, Perloff, et al., 2001; Bassuk et al., 1996; Browne & Bassuk, 1997; Buckner et al., 2004; Cowan, 2007; Guarino & Bassuk, 2010). However, studies have not been completed specifically documenting rates of PTSD among homeless children.…”
Section: The Needs Of Homeless Childrenmentioning
confidence: 99%
“…Ongoing chronic stress can have profound and lasting effects that may still be manifested in adulthood (Bassuk, 2007). Cowan's (2007) research has demonstrated that homelessspecific trauma accounts for a statistically significant variance in the mental health outcomes of sheltered children. Homeless children lose their sense of place, friends, pets, possessions, and sometimes their families (Bassuk, 2007).…”
Section: The Needs Of Homeless Childrenmentioning
confidence: 99%